Using the Past to Understand the Present: Coping with Natural and Anthropogenic Noise. (20th January 2021) - Gomes, Dylan G E; Francis, Clinton D; Barber, Jesse R
ABSTRACT: Anthropogenic noise has received significant attention in recent years, and researchers have highlighted the ways in which animals might deal with these noise sources. However, much of our understanding of animal responses to this novel source of background acoustics lacks an evolutionary perspective. Natural sources of noise predate the origin of hearing organs in animals. Therefore, it is unlikely that animals have only recently evolved strategies to cope with anthropogenic noise de novo but, rather, already have preexisting coping mechanisms, because of countless generations of evolution within a naturally noisy world, on which contemporary selection is now likely acting. We review strategies to cope with natural sources of noise and suggest a more quantitative and mechanistic understanding of how particular characteristics of noise have shaped animal populations and communities in the past, enabling us to predict the effects that novel sources of noise will have on the future.